2009
DOI: 10.5688/aj730595
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Lecture Delivery Platforms in a Hybrid Distance Education Program

Abstract: Objective. To compare students' preferences for and academic performance using 2 different distance education course content delivery platforms. Methods. A randomized, crossover research design was used to compare traditional video with a 4-panel platform among learners on multiple campuses within 1 college of pharmacy.1 The outcomes were students' preferences for delivery platform and examination scores. Rasch analysis was used to assess unidimensionality and the difficulty of examination items. Hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…[11][12][13][14] However, other studies have found comparable performances among students regardless of previous educational background, age, sex, or ethnicity. 15,16 Studies of the influence of educational background have found that the competitiveness and level of college attended prior to matriculation into a PharmD program added predictive value to PCAT scores and entering GPAs only for students' performance in the fourth year of pharmacy school. 17,18 Several other studies have found that pharmacy students with bachelor's degrees earned higher GPAs during their first year than did students with less prior education.…”
Section: Multiple Regression Analysesmentioning
confidence: 99%
“…[11][12][13][14] However, other studies have found comparable performances among students regardless of previous educational background, age, sex, or ethnicity. 15,16 Studies of the influence of educational background have found that the competitiveness and level of college attended prior to matriculation into a PharmD program added predictive value to PCAT scores and entering GPAs only for students' performance in the fourth year of pharmacy school. 17,18 Several other studies have found that pharmacy students with bachelor's degrees earned higher GPAs during their first year than did students with less prior education.…”
Section: Multiple Regression Analysesmentioning
confidence: 99%
“…Lecture capture had no effect on presentation grades, and while some studies reported higher examination grades, though not higher final grades compared to historical controls; others reported higher examination grades in historical controls. [6][7][8] The method of delivering the lecture capture was different among the 3 studies. One allowed the videos to be available for 72 hours, 6 1 used a 4-panel view for streaming the lectures, 7 and 1 used prerecorded lectures.…”
Section: Computer-aided Instructionmentioning
confidence: 99%
“…[6][7][8] The method of delivering the lecture capture was different among the 3 studies. One allowed the videos to be available for 72 hours, 6 1 used a 4-panel view for streaming the lectures, 7 and 1 used prerecorded lectures. 8 Additionally, 1 study reported that there was no difference in final course grades for the number of lectures viewed or the minutes of lectures viewed, although the average total number of accessions was low (3.4 out of 24 available).…”
Section: Computer-aided Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the medical field, "the universities that do not rise up to embrace this new technology will not survive long into the next century" (Harden & Hart, 2002, p. 262). The College of Pharmacy at the University of Florida doubled their enrollment when they implemented their hybrid program in 2002; at that time, the pharmacist shortage in the United Sates showed that there were thousands of pharmacist's positions open and not enough qualified pharmacists to fill them (Ried & Byers, 2009). By introducing a more flexible hybrid program, the College of Pharmacy at the University of Florida met both the academic needs of their students and the logistical needs of the field.…”
Section: Research On Hybrid Educationmentioning
confidence: 99%